Implementation of Islamic Business Ethics in the Management of Sharia Hotel Sumber Mulya, Nunukan Regency, North Kalimantan - Inayah Bulqis Rasyid; Irwan Misbach; Amiruddin K (Jurnal Manajemen Bisnis, 2023)
This research discusses the implementation of Islamic business ethics in the management of Sumber Mulya Syariah hotel in Nunukan Regency, North Kalimantan. In the analysis of sharia hotel management, it can be seen that the management is organized and structured, but the hotel does not yet have an SOP to maintain employee competency standards. Nevertheless, the application of Islamic business ethics values at Sumber Mulya Syariah hotel has been in accordance with the values of the principles of tawhid, justice, free will, ikhsan, and responsibility. The hotel prioritizes excellent service in accordance with the rules that have been made, respects the position as it should be in civilization, and strongly upholds trust and is responsible for problems that arise both between employees and hotel guests. However, the hotel is not yet officially registered as a Sharia Business Enterprise in Indonesia.